Faith, Reason, and Theosis - Demacopoulos, George E.; Papanikolaou, Aristotle (Book collections on Project MUSE., 2023)
"I keep getting this error message, but the description doesn't have any of the forbidden characters: "This field may contain characters that are not allowed. Your summary can contain only Latin characters. Do not include emoji, arrows, hearts, stars, checkboxes, symbols, faces, or bullets. Remove these characters and click Next to continue." See below for description"--